SIFAT FISIK DAN MEKANIK KAYU MENGKUDU (Morinda citrifolia L) BERDASARKAN DIAMETER DAN POSISI KETINGGIAN BATANG - Wahyuni, Sri; Usman, Fadiilah H; Nurhaida, . (Universitas Tanjungpura, 2019)
This study aims to determine the diameter and height position of noni wood that can produce the best physical and mechanical properties. The physical properties measured in this study were adjusted to their use, namely water content, density, and dimensional change using the standard British standard methods no. 373 (1999). Noni tree (Morinda citrifolia L) which is used in diameter 20 cm and 25 cm. Tree felling is carried out on branches as high as branch-free and 3 parts are taken, namely the base, middle, end where each part is 1 meter in size and the distance between parts is 1 meter. The three parts of the wood (base, middle, end) are made sticks measuring 2.5 x 2.5 x 1m. after that the stick is dried until it reaches a moisture content of 12-18%. This study used the Factorial Experiment pattern in Completely Randomized Design (CRD) with 2 treatment factors, namely a stem diameter of 25 cm, 20 cm, and height of stem (base, middle, end) so that 18 experimental combinations were obtained. The results showed that none wood (Morinda citrifolia L) was yellow ie 8/6 chroma value 2.5 Y and after being sprayed with a young cream color that is 7/4 Very Pale Brown 10 YR, until the old cream is 6/4 Light Yellowish Brown 10 YR based on Munsell 2000 with the best physical and mechanical properties is found in the diameter of 25 cm and the middle height of the stem with the value of water content 21.4690%, density 0.5500 gr / cm3, shrinkage 0.1122%, MOE 108810.37 kg / cm2, MOR 408,038.90 kg / cm2,MCS 280,00 kg/cm3 and included in the strong class category II-III.Keywords: Diameter, mechanical properties, noni, physical, the height position of a stem